Dimension‐Matched Zinc Phthalocyanine/BiVO4 Ultrathin Nanocomposites for CO2 Reduction as Efficient Wide‐Visible‐Light‐Driven Photocatalysts via a Cascade Charge Transfer. (19th July 2019) - Bian, Ji; Feng, Jiannan; Zhang, Ziqing; Li, Zhijun; Zhang, Yuhang; Liu, Yadi; Ali, Sharafat; Qu, Yang; Bai, Linlu; Xie, Jijia; Tang, Dongyan; Li, Xin; et al.
Abstract: Cascade charge transfer was realized by a H‐bond linked zinc phthalocyanine/BiVO4 nanosheet (ZnPc/BVNS) composite, which subsequently works as an efficient wide‐visible‐light‐driven photocatalyst for converting CO2 into CO and CH4, as shown by product analysis and 13 C isotopic measurement. The optimized ZnPc/BVNS nanocomposite exhibits a ca. 16‐fold enhancement in the quantum efficiency compared with the reported BiVO4 nanoparticles at the excitation of 520 nm with an assistance of 660 nm photons. Experimental and theoretical results show the exceptional activities are attributed to the rapid charge separation by a cascade Z‐scheme charge transfer mechanism formed by the dimension‐matched ultrathin (ca. 8 nm) heterojunction nanostructure. The central Zn 2+ in ZnPc could accept the excited electrons from the ligand and then provide a catalytic function for CO2 reduction. This Z‐scheme is also feasible for other MPc, such as FePc and CoPc, together with BVNS. Abstract : Räumlich angepasste Zink‐Phthalocyanin/BiVO4 ‐Nanoschicht‐Nanokomposite wurden entwickelt und sind effizienze, durch sichtbares Licht angetriebene Photokatalysatoren für die Umwandlung von CO2 in CO und CH4 . Die außergewöhnliche Aktivität wird der schnellen Ladungstrennung zugeschrieben, der ein Z‐Schema‐Ladungstransfermechanismus durch die angepasste ultradünne (ca. 8 nm) Hetero‐Junction‐Nanostruktur zugrundeliegt.